Response Surface Methodology to Optimize Laccase Produced from Pleurotus ostreatus Using Corn Cob and Rice Bran as Substrate - Hermansyah, Hermansyah; Gozali, Maftuh; Julinar, Julinar; Fanani, Zainal; Loekitowati Hariani, Poedji (Molekul, 2025)
ABSTRACT. Laccase is an industrially significant enzyme capable of oxidizing a broad range of phenolic compounds, making it valuable for applications such as bioremediation, textile dye decolorization, and pulp bleaching. Therefore, this study aimed to optimize laccase production from Pleurotus ostreatus using agricultural waste substrates corn cob (BJ), rice bran (DP), and their 1:1 mixture (BJ:DP) through Response Surface Methodology (RSM). Extracellular laccase was obtained by centrifuging the cultured medium, followed by ammonium sulfate precipitation and dialysis. The enzyme activity was quantified, and the fraction with the highest specific activity was analyzed using SDS-PAGE. Furthermore, Central Composite Design (CCD) was used to assess the effects of three independent variables, namely ABTS concentration (0.01–0.1 mM), incubation temperature (20–30 °C), and reaction time (20–30 minutes). The results showed that for BJ substrate, the highest enzyme activity (13.7 ± 0.05 U/mL) was observed in the 0–20% ammonium sulfate fraction, with specific activities of 76.25 ± 0.09 U/mg and 90.28 ± 0.03 U/mg in the 0–20% and 20–40% fractions, respectively. Conversely, DP substrate achieved a maximum specific activity of 209.67 ± 0.028 U/mg in the 20–40% fraction. The crude extract from BJ:DP mixture showed a high protein content (0.636 ± 0.006 mg/mL) but the specific activity was substantially lower (19.33 ± 0.003 U/mg). Based on RSM analysis, the optimal conditions were ABTS concentration of 0.05 mM, incubation temperature of 22.21 °C, and reaction time of 28.64 minutes, resulting in a predicted laccase activity of 13.99 U/mL. Keywords: Corn cob, Laccase, Pleurotus ostreatus, Response Surface Methodology, Rice bran